(untitled) (CIPEEX, 2024)
This work explores the dynamics of the judicialization of social relations in Brazil, examining its causes, consequences and challenges. The analysis suggests that growing distrust in political institutions and the search for justice lead to an increase in legal demands, impacting the efficiency of the judicial system. The literature review highlights the need to strengthen political institutions and promote alternatives to judicialization, such as conflict resolution mechanisms and civic education. The union of efforts between different social actors and the implementation of public policies are seen as essential to guarantee a healthy balance between the protection of rights and the efficiency of the legal system, in addition to strengthening democracy. Based on this, the objective of this work is to analyze the growing judicialization of social relations in Brazil and its impacts on society and the legal system. Judicialization refers to the phenomenon where social, political and economic issues are taken to the Judiciary for resolution. This study uses the literature review method to explore the causes and consequences of this phenomenon. It is observed that judicialization is associated with distrust in political institutions and the search for rights through the Judiciary. Although it can guarantee the protection of individual and collective rights, judicialization also overloads the judicial system and can lead to the politicization of judicial decisions. One of the results found was that the proliferation of legal demands directly impacts the efficiency of the judicial system, increasing the processing time of processes and the associated costs. Furthermore, judicialization can shift the resolution of social issues from the political to the legal sphere, which can weaken the role of democratic institutions. The search for alternatives to judicialization is crucial. This includes strengthening political institutions, promoting alternative conflict resolution mechanisms, and civic education for greater citizen participation in political decisions. Dialogue between different social actors and the adoption of effective public policies are essential to reduce dependence on the Judiciary in resolving social conflicts. It is concluded that the judicialization of social relations is a complex phenomenon that demands a multidisciplinary approach to balance the protection of rights and the efficiency of the judicial system, in addition to strengthening democratic institutions.